São Luiz do Paraitinga: The Image of São Paulo State in the 18th Century - Pereira de Campos, Rogério; Rodrigues, Maria Fernanda; Costa, Anibal; Varum, Humberto (Protection of Cultural Heritage, 2021)
São Luiz do Paraitinga it is a city anchored on time, a unique register of São Paulo State about modern concepts reformulation, proposed by Marquês de Pombal in the 18th century for Portugal and its colonies. Isolated between mountain-chains with strategic position, it was built as a trading post to favour the gold and other products transportation to Portugal and also to increase Portuguese Empire control over the Brazilian goods production. It remains generally preserved due to its forgetfulness, after the favourable periods of the local economy, remaining static. But its heritage degradation and destruction was also due of forgetfulness and lack of protection of the Brazilian State. São Luiz do Paraitinga constructive process and culture of 18th century is a singular case that will be analysed in this paper, bringing evidences about the common people life in the Portuguese colony, and not only about State Rulers and great owners.